Sistem Informasi Hutang Piutang (Studi Kasus:Perusahaan XYZ) - Eko Purwanto; Hanifah Permatasari (Politeknik Indonusa Surakarta, 2020)
XYZ Company in the process of delivering receivable payable information is done by the way, the Director came directly to the company to know the due date receivable payable still using the manual system by admin seeing the accounts payable one by one. As a result, the information of due date receivable payables is less quickly submitted to the owner of the company. The puspose of designing and building a system of receivable payable information on Batik Rahmawati Company is, that the system expected would provide quickly and correctly information to the company. In this research, the researcher proposed the use of web-based accountspayable information system to provide receivable payable information to owner and the due date of receivable payable information of the accounts payable to the supplier or customer. The system that has been used is developed to computerize based (towards computerization) by using online web and using the waterfall development system method and by using designtools DFD ( Data Flow Diagram ). The testing is done by using Black box test which gives result that the web run as expected. The testing user who gives result agrees thet the system of the receivable payable information is feasiable and could help the user knowing the amount of the due date receivable payable. The conclusion of we-based receivable payable system is, that application could facilitate easilythe owner, suppliers, costomers of XYZ Company to know the receivable payable.